Conceptualizing Childbearing Ambivalence: A Social and Dynamic Perspective. Issue 4 (9th May 2018) - Sennott, Christie; Yeatman, Sara
Abstract : Childbearing ambivalence is often conceptualized as a state of conflicting desires about having a child that is characteristic of particular individuals or life stages. This study proposes that childbearing ambivalence is dynamic and situational, resulting from the multiple sociocultural frames surrounding childbearing. Using eight waves of prospective data from a population‐based sample of young adults in Malawi, results show that 41% of women and 48% of men are ambivalent about childbearing at some point in the 2.5‐year study. There is limited evidence that ambivalence is related to individual sociodemographic or psychosocial characteristics aside from gender; rather, ambivalence is tied to life course markers such as school enrollment and age. In addition, life course transitions and changes in relationships, health, and economic factors are associated with the onset of ambivalence, supporting the theory that ambivalence is a dynamic state that men and women frequently pass through as their lives and circumstances change.